EXTROVERT-INTROVERT STUDENTS AND THEIR ENGLISH SPEAKING PERFORMANCE - Putri Septianah; Endang Susilawati; Iwan Supardi (Universitas Tanjungpura, 2019)
Abstract This research aimed to investigate how high the correlation of Extrovert-Introvert personality towards speaking performance of the 2018 academic year students of Speaking for Academic Presentation class of English Education Study Program in Teacher Training and Education University of Tanjungpura. The sample of this research was 20 students of Speaking for Academic class which consists of 20 females and 5 males in the class. The measurement of personality and speaking performance were determined by using Mark Parkinson Personality Questionnaire (MSQ) and Monroe’s motivated persuasive rubric score. The students’ personality and speaking score were correlated by using Pearson Product Moment and Multiple Correlation formula. The result of this research show the correlation between extrovert-introvert personality in speaking performance is 0.5206 that indicate moderate correlation between these variables. The result for the sub-correlation between extrovert and speaking performance is 0.4183, introvert and speaking performance is 0.4096 which both also shows moderate correlation. From this research, the researcher had conclusion that extrovert-introvert personality has the effect to the speaking performance.Keywords: Extrovert Personality, Introvert Personality, Speaking Performance